2016
DOI: 10.1097/md.0000000000005644
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors analysis of consecutive exotropia

Abstract: To evaluate clinical factors associated with the onset of consecutive exotropia (XT) following esotropia surgery.By a retrospective nested case-control design, we reviewed the medical records of 193 patients who had undergone initial esotropia surgery between 2008 and 2015, and had follow-up longer than 6 months. The probable risk factors were evaluated between groups 1 (consecutive XT) and 2 (non-consecutive exotropia). Pearson chi-square test and Mann–Whitney U test were used for univariate analysis, and con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…3.47± 5.36 years. In contrary to Gong, Q.et al [9] who reported a mean interval between the initial surgery and the XT operation was 37 (range, 1-90) months. On the other hand, Gesite et al [7] reported that the mean interval between surgery for esotropia and consecutive exotropia was 14.6± 19.3 years.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…3.47± 5.36 years. In contrary to Gong, Q.et al [9] who reported a mean interval between the initial surgery and the XT operation was 37 (range, 1-90) months. On the other hand, Gesite et al [7] reported that the mean interval between surgery for esotropia and consecutive exotropia was 14.6± 19.3 years.…”
Section: Discussionmentioning
confidence: 68%
“…Consecutive exotropia (XT) is a manifest exotropia that develops either spontaneously or after optical or surgical treatment in a patient that formerly had esotropia (ET). It has been reported in 4% to 27% of patients after surgical treatment of exotropia [9] . Our study included 30 patients (16 females and 14 males) with established diagnosis of consecutive exotropia after surgery for esotropia with deviation angle ≥ 10 PD, aged from 3 to 25 years with the Mean age±SD was 11.07± 6.26 years .…”
Section: Discussionmentioning
confidence: 99%
“…Ceylan et al ( 11 ) reported that 26.7% of the CXT group showed inferior oblique muscle overaction compared to 7.4% of the nonexotropic group. Oblique dysfunction leads to orthotropic instability and is not beneficial for long-term alignment, which may even accelerate the development of misalignment ( 12 ). Our results highlighted the strong influence of vertical deviation in affecting long-term alignment.…”
Section: Discussionmentioning
confidence: 99%